Analisis Fraktal Untuk Menentukan Kuat Geser Batuan Sedimen di Kabupaten Ende - Lianunu Provinsi Nusa Tenggara Timur - Indonesia - Tien Veny Vera; Sari B Kusumayudha; Singgih Saptono; Kurniawan Kurniawan (Jurnal Geomine, 2023)
Rock surface roughness is an important parameter used in calculating the shear strength of rocks, both of which greatly affect the stability of a slope. In this research, direct shear strength testing was carried out on 5 sedimentary rocks to obtain the value of cohesion and internal friction angle. The research objectives include (1) Calculating the fractal dimension (D), joint roughness coefficient (JRC), and rock shear strength. (2)Analysis of rock shear strength calculation results from rock direct shear test results. To determine the fractal dimension using the box-counting method in ImageJ FracLac software. The factual D and JRC are two interrelated parameters, where the higher of D value, will increase the JRC value, this is influenced by the grain size. In the fine grain size sample, the D values ranged 1.0034-1.0045, medium grain size 1.0057, and coarse grain size 1.0084-1.0085. Calculations with the new equation, the JRC values in the samples S1 (8-10), S2 (12-14), S3 (4-6), S4 (12-14), and S5 (6-8). The comparison of graphs shows a pattern that is almost similar to previous researchers. The difference in the value of shear strength is influenced by the level of rock surface roughness using fractal dimensions provides a higher detail value. By using statistical analysis (RMSE and MAD), it shows a small error value, namely the results of the research which have the lowest RMSE (0.14) and MAD (0.11) values, meaning the results of calculations using fractal dimensions are correlated with the measured data from the laboratory shear test.